The event of postcolonial shame - Bewes, Timothy (Translation/transnation., 2011)
Argues that shame is a dominant temperament in twentieth-century literature, and the key to understanding the ethics and aesthetics of the contemporary world. This title states that the practices of postcolonial literature depend upon and repeat the same structures of thought and perception that made colonialism possible in the first place.